Using Targeted Nano-Antibiotics to Improve Antibiotic Efficacy against Staphylococcus aureus Infections - Hung Le; Emmanuelle Dé; Didier Le Cerf; Carole Karakasyan (MDPI AG, 2023)
The poor bioavailability of antibiotics at infection sites is one of the leading causes of treatment failure and increased bacterial resistance. Therefore, developing novel, non-conventional antibiotic delivery strategies to deal with bacterial pathogens is essential. Here, we investigated the encapsulation of two fluoroquinolones, ciprofloxacin and levofloxacin, into polymer-based nano-carriers (nano-antibiotics), with the goal of increasing their local bioavailability at bacterial infection sites. The formulations were optimized to achieve maximal drug loading. The surfaces of nano-antibiotics were modified with anti-staphylococcal antibodies as ligand molecules to target S. aureus pathogens. The interaction of nano-antibiotics with the bacterial cells was investigated via fluorescent confocal microscopy. Conventional tests (MIC and MBC) were used to examine the antibacterial properties of nano-antibiotic formulations. Simultaneously, a bioluminescence assay model was employed, revealing the rapid and efficient assessment of the antibacterial potency of colloidal systems. In comparison to the free-form antibiotic, the targeted nano-antibiotic exhibited enhanced antimicrobial activity against both the planktonic and biofilm forms of S. aureus. Furthermore, our data suggested that the efficacy of a targeted nano-antibiotic treatment can be influenced by its antibiotic release profile.